Indicators of Mothers’ Knowledge Regarding Completeness of Basic Imunization for Children Aged 0-24 Months in Kota Tengah Public Health Centre, Gorontalo - Indrawati Indrawati; Dewi Modjo; Ariel Syafrianto Haruna (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Immunization is a crucial preventive measure to protect children from infectious diseases. A significant decline in coverage is often influenced by the role of mothers as the primary decision-makers in children's health.This study aimed to describe maternal knowledge indicators and their relationship with the completeness of basic immunization for children aged 0-24 months. Utilizing a quantitative design with a cross-sectional approach, the study was conducted on 42 respondents in the Kota Tengah Public Health Center work area, selected through accidental sampling. Data were collected using knowledge questionnaires and Maternal and Child Health (MCH) books, and then analyzed descriptively and using the Chi-square test. The results show that while the majority of mothers understand the definition of immunization, approximately one-third of respondents still have misconceptions regarding the types, benefits, and schedules of vaccinations. Statistical tests reveal a significant relationship between the level of maternal knowledge and immunization completeness (p=0.001), where mothers with better knowledge tend to be more compliant in completing their children's immunization status. In conclusion, maternal knowledge is a vital determinant in the success of immunization programs. More comprehensive health education strategies and continuous guidance for parents are highly necessary to raise awareness and ensure optimal child health protection at the public health center level.